Lighting System Energy Optimization and Savings Potential: A Case Study at the Polytechnic Library - Arifia Ekayuliana; Andi Ulfiana; Yulimafendro Dedet Eka Saputra; Ikhbar Ramadhan; Adam Hidayat (Faculty of Engineering, Universitas Muhammadiyah Jakarta, 2025)
The rising electricity consumption in Indonesian buildings highlights the critical importance of energy efficiency. Lighting systems, especially in libraries, account for a significant portion of overall building energy use. However, fewer than 5% of university libraries in Indonesia publish their energy audit data, indicating a scarcity of studies based on actual field measurements. This study is the first to utilize direct measurement data from the Politeknik Negeri Jakarta (PNJ) Library to evaluate its lighting system and identify potential energy savings. A quantitative audit was conducted by collecting data on room dimensions, lamp specifications, lighting points, and operating hours. The existing installations of Tubular Light Emitting Diodes (TLED, 8 W) and Light Emitting Diodes (LED, 13 W) were compared against the minimum illuminance standards defined by the Indonesian National Standard (SNI). The results revealed instances of excessive lighting, with potential savings of 37.8 kWh/month on the first floor and 32.3 kWh/month on the second floor. In this retrofit scenario, no replacement of lamp types was undertaken to avoid additional investment costs. Instead, optimization was achieved by adjusting the number of luminaires based on the SNI minimum lux standard to achieve optimal energy efficiency while maintaining illumination quality. These findings offer practical insights for building managers in implementing energy conservation strategies and serve as a reference for future studies integrating occupant-based lighting control systems.